Environmental contexts and disability - Barnartt, Sharon N.; Altman, Barbara Mandell (Emerald, 2014)
Physical structure, economic expectation or social relationship norms developed within various cultures can either restrict or support the participation of individuals with disabilities in society. The influence of environmental factors can vary significantly according to context, characteristics or by action difficulty. The objective of this volume is to identify and address environmental issues that support or restrict the participation of persons with functional limitations in society, either at the micro, meso or macro levels. The papers address both individual, societal, national and international levels of environment and shed new light on the processes involved with creating or modifying these environmental supports or barriers. Several papers approach the societal and intra-societal levels. The volume is separated into four parts; part one focuses on the larger disability environment from an international, national and community perspective, the second includes important theoretical and methodological approaches; section three highlights reviews of the environmental literature and the final section addresses personal experience with environmental barriers.
Keywords: Social Science -- People with Disabilities.; Social Science -- General.; Disability: social aspects.; People with disabilities -- Social aspects.; Barrier-free design.; elektronické knihy; electronic books